2021
DOI: 10.3389/fevo.2021.748870
|View full text |Cite
|
Sign up to set email alerts
|

Floral Resources Enhance Fecundity, but Not Flight Activity, in a Specialized Aphid Predator, Hippodamia convergens (Coleoptera: Coccinellidae)

Abstract: Adult aphid predators disperse across the landscape seasonally in search of prey aggregations that are patchily distributed and temporally variable. However, flight is energetically costly and consumes resources that could be invested in reproduction. Hippodamia convergens is an important aphid predator in North American cereal crops and other agricultural systems. Consumption of floral resources can enhance adult survival during periods of low prey availability and may improve reproductive success. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…These species are common in other Portuguese crops, such as chestnut, almond, or olive groves [31,43,72]. Scymnus apetzi and S. interruptus were also frequent species in Portuguese citrus groves [45], preying mainly on aphids [27,39,41]. Their high abundance in olive and citrus groves suggested that they probably feed on the black scale, S. oleae, a frequent coccid pest in both crops, as well as other coccids and pseudococcids [31,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These species are common in other Portuguese crops, such as chestnut, almond, or olive groves [31,43,72]. Scymnus apetzi and S. interruptus were also frequent species in Portuguese citrus groves [45], preying mainly on aphids [27,39,41]. Their high abundance in olive and citrus groves suggested that they probably feed on the black scale, S. oleae, a frequent coccid pest in both crops, as well as other coccids and pseudococcids [31,44].…”
Section: Discussionmentioning
confidence: 99%
“…This tribe is mainly composed by predators of aphids [74], psyllids, and Chrysomelidae [27]. It includes C. septempunctata, the third more abundant species in the study, which besides aphids [39], feed on pollen [27]. In Portugal, this species is frequent in chestnuts [43], citrus groves [45], and almond trees [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corn and soybean fields can be heavily colonized by aphids and thus provide abundant prey for lady beetles, but this is only the case during limited time periods; over long periods such fields are characterized by resource scarcity, e.g., before crop emergence, after crop maturity, or after pesticide application (Rand et al 2006;Schellhorn et al 2014;Iuliano and Gratton 2020). In landscapes that are strongly dominated by a few crop monocultures, these periods are synchronized over large areas and habitat patches with alternative food sources are often far away and only accessible at high energetic costs (Bonte et al 2012;Stowe et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…The omnivorous behavior of predatory ladybird beetles is mainly driven by an appetite for nutrients, such as sterols found in the foliage 5–7 . Consequently, supplementary consumption of plant‐derived foods is therefore often necessary for the beetles to achieve maximal fitness 2,8,9 . For example, a significantly reduced preoviposition period and a substantial increase in 21‐day fecundities were observed in Hippodamia convergens Guérin‐Méneville (Coleoptera: Coccinellidae) when eating an omnivorous diet consisting of sugars, pollen, seedling wheat leaves, and eggs of Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae) compared to feeding solely on the monotypic aphid prey, Schizaphis graminum (Rondani) (Hemiptera: Aphididae) 9 .…”
Section: Introductionmentioning
confidence: 99%